2012
DOI: 10.4209/aaqr.2011.07.0102
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the Ozone Weekend Effect in Tokyo, Japan: Regime of Oxidant (O3 + NO2) Production

Abstract: The ozone weekend effect (OWE) in Tokyo, the capital of Japan, was analyzed from April 2005 to March 2008 with respect to the photochemical ozone production, focusing on the ozone production regime. For most periods, the OWE was confirmed in the wintertime as well as in the summertime.concentrations between weekdays and weekends suggests that there are some periods when the photochemical ozone production on the weekends could be larger than on the weekdays (defined as the POP group). We compared NO x (the sum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…On the 11th of May, O 3 steeply declined after 19:00 h with a reduction rate of 14 ppbv/h compared to the control day (8 ppbv/h). It was reported that the reduction in O 3 occurs in the presence of a high concentration of NO x specifically in the urban lower tropospheric region (Debaje and Kakade 2006;Sadanaga et al 2012). In addition to this, reduced VOC/NO x ratios can also cause reduction of O 3 by titration reaction due to high emission of NO (Swamy et al 2012) resulting to the formation of NO 2 and O 2 .…”
Section: Variations In Surface O 3 and No X During Thunderstorms In Tmentioning
confidence: 98%
“…On the 11th of May, O 3 steeply declined after 19:00 h with a reduction rate of 14 ppbv/h compared to the control day (8 ppbv/h). It was reported that the reduction in O 3 occurs in the presence of a high concentration of NO x specifically in the urban lower tropospheric region (Debaje and Kakade 2006;Sadanaga et al 2012). In addition to this, reduced VOC/NO x ratios can also cause reduction of O 3 by titration reaction due to high emission of NO (Swamy et al 2012) resulting to the formation of NO 2 and O 2 .…”
Section: Variations In Surface O 3 and No X During Thunderstorms In Tmentioning
confidence: 98%
“…This is relatively easy to identify, so received comment in Victorian cities where pollution was argued to derive from cooking Sunday roast dinners (Brimblecombe, 1987). Today, pollutants such as CO, NOx, NO2, SO2 and PM2.5,10 are typically found to be higher on weekdays, because of rush hour traffic, work patterns and industrial activities, but also influenced by population and urbanization (Qin et al, 2004;Riga Karandinos, 2005;Pudasainee et al, 2010;Sadanaga et al, 2012;Wolf et al, 2013;Cerro et al, 2014;Porter et al, 2014;Henschel et al, 2015;Malik et al, 2015;Martins et al, 2015). Ozone as a secondary photochemical oxidant, shows more complex behavior: lower on weekdays than on weekends (Tang et al, 2008), although sometimes it can also be higher during the week (Huryn et al, 2014;Xie et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…OH + NO 2 + M → HNO 3 + M. (11) Hence the relationship between ozone formation and precursor concentrations is non-linear and complex. An example of the complexity is the ozone production regime, which consists of "NO x -limited" and "VOC-limited" (or NO x -saturated) regimes.…”
Section: Introductionmentioning
confidence: 99%